Answer:
(x,y) = (-1,4)
Explanation:
y = y right? So all you have to do is replace both of the equations.
![-x+3=x+5\\-x-x=5-3\\-2x=2\\x=-1](https://img.qammunity.org/2021/formulas/mathematics/college/ycbxfqwkoyc3qaa5ir8nccrvmaojpczavw.png)
after you've found the value of x just substitute it into ANY of these two equations!
For example if we get the first one we have
![y=-(-1)+3\\y=1+3\\y=4](https://img.qammunity.org/2021/formulas/mathematics/college/1z7dcq20j6g14wu64ewlgg0fqc8ow7qnpu.png)
And there you have it. Hope it helps!